Financial Market Liberalisation, Wealth and Consumption - Boone, Laurence (OECD Economics Department Working Papers, 2001)
The past two decades have seen substantial deregulation in the financial sectors of most OECD countries. The main motivation was to improve efficiency within the financial system, but the macroeconomic implications might go beyond this objective with impacts on the business cycle and the transmission mechanisms of monetary and fiscal policies. More specifically, financial liberalisation and heightened competition in the financial services sector, through a rapid expansion of credit, may have eased the liquidity constraints facing households, thus raising the targeted level of consumption. The objective of this paper is to test whether financial deregulation, through an easing of liquidity constraints, has had an impact on the relationship between consumption and income, and more specifically on the wealth effect. A range of different procedures is used to assess the impact of financial deregulation on global wealth and on its different components (financial, housing and others) ...